Predicting the risk of cardiac myxoma in Carney Complex - Pitsava, Georgia (Genet Med, 2020)
PURPOSE: Carney complex (CNC), is an autosomal dominant multiple neoplasia and lentiginosis syndrome. We aimed to identify risk factors associated with the occurrence and recurrence of cardiac myxomas, the predominant cause of death in CNC patients. METHODS: Patients with CNC were monitored prospectively between 1995 and 2020 for the development of cardiac myxomas. RESULTS: Of the 319 patients studied, 136 (42.6%) developed myxomas. The mean age at diagnosis was 28.7 ± 16.6 years in females and 25.0 ± 16.4 years in males. By age 30, 35% of females and 45% of males had at least one myxoma. The CNC-related lesions: lentigines, cutaneous, mucosal, or breast myxomas, thyroid nodules, pituitary adenoma, and schwannoma were significantly more frequent (all p<0.05) among patients with myxomas. Forty-four percent of patients had recurrences; nearly all within the first 8 and 16 years for males and females, respectively. Recurrences were more common in females. CONCLUSION: This is the largest study to date and provides the first-time risk estimates by age and gender for cardiac myxomas in CNC patients. Cardiac myxomas are common by age 30 and often recur, especially in women, but the risk drops in 10 to 20 years. These findings may guide the patient counseling, screening intervals and surgical approaches.